An investigative study of customers’ experience in customized customer contact services in Oporto hotels - Maria Nascimento Cunha, PhD (African Journal of Hospitality, Tourism and Leisure, 2019)
Several hospitality industry operations face the concerns of coordinating and organizing a customized customer contact service point for their customers, especially with the connection with the customer preference and details. Hence, customers experience some series of intermittent communications when they come across various contact points within the hospitality industry. Thus, the purpose of this study was to concentrate on ascertaining the impact of customized customer contact services on customer’s experience in the Oporto hospitality industry in Portugal. The study investigated two hundred participants, who are guests of hospitality industries in Oporto. The study adopted a descriptive analysis method to find the overall result of the study. The study further adopted T-test and ANOVA to carry out the analysis for this research. Findings from this work shows that guests of the hospitality industry highly acknowledged the importance of a customized contact service point and its positive impact on their lives. The study further showed that there is a significant difference between income of guests and how it impacts on their experience towards a customized contact point. Other findings showed that both age and gender of the customer does not necessarily impact on their experience towards a customized customer service contact point; thus the study shows no significant differences.